The role of universities in community development: Lessons from the environmental education and sustainability project at Mangosuthu University of Technology — A cross-sectional mixed-methods study. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Higher education institutions play a pivotal role in promoting community development and advancing sustainability. Yet, aligning academic programs with local community needs remains a challenge. This study examines the Environmental Education and Sustainability Project at Mangosuthu University of Technology (MUT), which seeks to empower marginalized communities through environmental education and sustainable living practices. Methods A mixed-methods approach was adopted. Quantitative data were collected through pre- and post-intervention surveys assessing environmental knowledge and awareness. Qualitative data were obtained from focus group discussions and in-depth interviews with project participants, including community members, educators, and students. Results A total of 120 participants (58% female, 42% male; ages 18–55) were involved. The majority (75%) resided in Umlazi Township. Post-intervention surveys revealed significant improvements: understanding of waste management increased from 35% to 78%, water conservation awareness from 30% to 72%, and knowledge of local biodiversity from 25% to 68% (p < 0.01). Qualitative analysis highlighted behavioural change and community empowerment. Participants reported adopting sustainable practices: “I now teach my children how to save water and separate waste.” Educators incorporated environmental topics into their teaching: “I have started including environmental topics in my lessons.” The project also strengthened university-community trust: “Now we see how the university can help our community.” Conclusion The project effectively bridged academic learning with real-world community engagement. It enhanced environmental literacy, promoted behavioural change, and fostered stronger university-community partnerships. Recommendations Higher education institutions should embed community-focused environmental education into their curricula, promote local knowledge integration, and support ongoing stakeholder engagement. The MUT model provides a scalable framework for universities seeking to align academic missions